ANALISIS CLUSTER KECAMATAN DI LOMBOK TIMUR BERDASARKAN BANYAKNYA PERUSAHAAN DAN CABANG INDUSTRI - Sopiana Indra Wardani; Wiwit Purwa Nurmayanti; Muhammad Malthuf (Institut Teknologi Statistika dan Bisnis Muhammadiyah Semarang, 2020)
Cluster analysis is a technique used to classify objects into relatively homogeneous groups. In 2018 the number of companiesand industrial branches in East Lombok regency has been recorded by BPS, but there are no sub-district clusters for eachindustry. The purpose of this study is to clustering 21 sub-districts in East Lombok Regency in 2018 based on the number ofcompanies and branches of industry comprising the metal machinery and engineering, electronics and miscellaneous industriesand the textile industry. The results of the analysis using cluster analysis with the Single Linkage method shows information thatthe sub-district group comprised three groups, namely the sub-district group with many of the highest, medium and lowestindustries. Companies and branches of the metal machinery and engineering and electronics and miscellaneous are found in theDistrict of Selong, and for the most textiles in the Districts of Pringgasela, Aikmel and Lenek.